Bifacial cambium stem cells generate xylem and phloem during radial plant growth - Shi, Dongbo; Lebovka, Ivan; Greb, Thomas (Development, 2019)
A reduced rate of stem cell division is considered a widespread feature which ensures the integrity of genetic information during somatic development of plants and animals. Radial growth of plant shoots and roots is a stem cell-driven process that is fundamental for the mechanical and physiological support of enlarging plant bodies. In most dicotyledonous species, the underlying stem cell niche, the cambium, generates xylem inwards and phloem outwards. Despite the importance and intriguing dynamics of the cambium, the functional characterization of its stem cells is hampered by the lack of experimental tools for accessing distinct cambium sub-domains. Here, we use the hypocotyl of Arabidopsis thaliana to map stem cell activity in the proliferating cambium. Through pulse labeling and genetically encoded lineage tracing, we find that a single bifacial stem cell generates both xylem and phloem cell lineages. This cell is characterized by a specific combination of PXY (TDR), SMXL5 and WOX4 gene activity and a high division rate in comparison with tissue-specific progenitors. Our analysis provides a cellular fate map of radial plant growth, and suggests that stem cell quiescence is not a general prerequisite for life-long tissue production.
Gesehen am 24.01.2019